Analysis of the Impact of Tax Amnesty, Tax Knowledge, Taxpayer Services, Tax Awareness, and Tax Sanctions on Taxpayer Compliance - Yanti, Lina; Patiro, Shine Pintor S.; Rahayu, Heffi Christya (PINISI Discretion Review, 2025)
The purpose of this study is to examine the influence of the tax amnesty program, tax knowledge, tax services, tax awareness, and tax sanctions on taxpayer compliance at the Batam Utara Primary Tax Office (KPP Pratama Batam Utara). The type of research used in this study is causal-comparative research. This research employs a quantitative approach. The population in this study consists of 306,230 taxpayers, and the sample includes 300 taxpayers. The data used consists of primary and secondary data. Data analysis techniques in this study include descriptive analysis and multiple linear regression analysis. The researcher also used classical assumption tests such as normality test, linearity test, multicollinearity test, and heteroscedasticity test. Based on the research findings, it was found that tax amnesty and tax sanctions have a positive and significant impact on taxpayer compliance at the Batam Utara Primary Tax Office. The researcher also found that the variables of tax knowledge, tax services, and taxpayer awareness did not have a positive and significant impact on taxpayer compliance at the Batam Utara Primary Tax Office. Future research could add other independent variables that affect taxpayer compliance, such as education level, tax administration system, tax rates, tax audits, tax law enforcement, and other variables. Future research could also be conducted after the third round of the tax amnesty, which is planned to take place in 2025.